Nouvelles données sur un assemblage ostéoarchéologique en lien avec la première pandémie de peste historique : la nécropole tardo-antique du "Clos des Cordeliers" à Sens (Yonne, France) - Marion Holleville; Dominique Castex; Marie-France Deguilloux; Sacha Kacki (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Research on historical plague epidemics has undergone a major revival in recent decades, thanks in particular to the growing number of archaeo-anthropological studies on material evidence. However, while much has been published on burial sites associated with the second plague pandemic (14th-18th centuries AD), those dealing with the first plague pandemic (6th-8th centuries AD) remain rare. In this respect, the "Clos des Cordeliers" burial site in Sens (Yonne) offers a rare opportunity. The 1989 excavation revealed the presence of four large Late Antiquity mass graves, which were subsequently shown to be linked to a plague epidemic through palaeogenetic analysis. Despite the exceptional nature of this burial site and the time elapsed since its discovery, up until now it had only been partially studied. This led us to conduct a detailed anthropological re-examination of the 78 individuals making up the sample. Our aim was to characterise this osteological assemblage from a biological perspective and to assess the pre-existing health status of the plague victims through the study of non-specific stress indicators. Comparison of the results with data from burial assemblages associated with the second plague pandemic reveals some differences with the latter (differences in sex ratio, lower mortality in adolescents), raising questions about possible variations in the epidemiology of the plague between these two pandemics.